The role of genetic variation in shaping phenotypic responses to diet in aging Drosophila melanogaster. - Bak, N.K.; Mackay, T.F.C.; Morgante, F.; Nielsen, K.L.; Nielsen, J.L.; Kristensen, T.N.; Rohde, P.D. (Heredity, 2025)
Nutrition plays a central role in healthy living, however, extensive variability in individual responses to dietary interventions complicates our understanding of its effects. Here we present a comprehensive study utilizing the Drosophila Genetic Reference Panel (DGRP), investigating how genetic variation influences responses to diet and aging. We performed quantitative genetic analyses of the impact of reduced nutrient intake on lifespan, locomotor activity, dry weight, and heat knockdown time (HKDT) measured on the same individual flies. We found a significant decrease in lifespan for flies exposed to a restricted diet compared to those on a control diet. Similarly, a notable reduction in dry weight was observed in 7 and 16-day-old flies on the restricted diet compared to the control diet. In contrast, flies on the restricted diet exhibited higher locomotor activity. Additionally, HKDT was found to be age-dependent. Further, we detected significant genotype-by-diet interaction (GDI), genotype-by-age interaction (GAI) and genotype-by-age-by-diet interaction (GADI) for all traits. Thus, environmental factors play a crucial role in shaping trait variation at different ages and diets, and/or distinct genetic variation influences these traits at different ages and diets. Our genome-wide association study also identified a quantitative trait locus for age-dependent dietary response. The observed GDI and GAI indicate that susceptibility to environmental influences changes as organisms age. These findings could have significant implications for understanding the genetic mechanisms underlying dietary responses and aging in Drosophila melanogaster, which may inform future research on dietary recommendations and interventions aimed at promoting healthy aging in humans. The identification of associations between DNA sequence variation and age-dependent dietary responses opens new avenues for research into the genetic mechanisms underlying these interactions.